Diagnostic Accuracy of Urine Dipstick for Diagnosis of Preeclampsia - Asma Qayyum, Rubina Iqbal, Rafia Ali (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the diagnostic accuracy of urine dipstick for diagnosis of preeclampsia in females with gestational hypertension taking 24hours urinary protein as gold standard Methodology: In this Cross sectional study conducted at, Unit III, Department of Obstetrics & Gynecology, Fatima Memorial Hospital Lahore during the year 2019. A total 100 females fulfilling the inclusion criteria were included through OPD. Then females were given a sterile container to collect the urine sample. Dipstick was dipped in urine sample for 1-2 minutes. Results of dipstick was noted and patients were labeled as positive or negative. Then females were admitted in gynecology wards for 24 hours to collect urine sample in collection bag. After 24 hours, complete sample was sent to the laboratory of the hospital for assessment of urinary protein level. Reports were assessed and patients were confirmed as positive or negative. Females with preeclampsia were managed as per hospital protocol. Results: According to urine dipstick test preeclampsia was diagnosed in 63(63%) women. According to 24 hours urinary protein criteria preeclampsia was diagnosed in 54(54%) women. Sensitivity and specificity of urine dipstick test was 90.74% and 69.5%. While PPV &NPV were 77.78% and 86.49% respectively. Diagnostic accuracy of urine dipstick was 81%. Conclusion: The diagnostic tests accuracy of urine dipstick for diagnosis of preeclampsia in females with gestational hypertensionis reliable, relatively faster and accurate.It is also concluded that it is much more reliablethan 24hours urinary proteintest.